Distribution Of Abo And Rh Blood Groups In Hiv Seropositives At An Integrated Counseling And Testing Centre In Karnataka, India - Banu, A; Ahmed, SM; Shastri, S (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: ABO blood group system was the fi rst human blood group system to be discovered. Subsequent to the discovery of blood groups by Landsteiner and advancement in its study many workers tried to fi nd out associations between blood groups and the incidence of various diseases. The objective of the study was to create a blood group database which would probably help in transfusion services and fi nd out the distribution of blood groups in the seropositive population. Methodology: Blood groups were ascertained for 1809 patients who were HIV seropositive enrolled at ICTC in a tertiary care teaching hospital in Karnataka, India from April 2004 to January 2010 using the simple tile method. The results were compiles and statistically analyzed. Results: Blood grouping was done for 1809 patients, out of which 1749 (96.68%) were adults and 60(3.32%) were paediatric patients. O Rhesus positive was the most prevalent blood group in both adult (40.13%) and paediatric (43.33%) seropositives. B Rhesus positive was next commonest group in adults (26.12%) and A Rhesus positive in paediatric(30.0%). AB Rhesus negative (Adults-0.34% and Paediatric-0%) blood group was the least prevalent in the study population. Conclusion: It is important to create blood group database for the Indian seropositives population, to know any probable association between blood group and HIV infection. This study is an attempt to create a blood group database in a modestly large seropositive which would play a vital role in transfusion services and future research . Larger nation-wide studies would be required to substantiate any association between blood groups and HIV infection. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5901 SAARCTB 2011; 8(2): 42-45